Hydrogen purification using nanoporous graphene membranes and its economic analysis. (23rd November 2019) - Sun, Chengzhen; Zheng, Xiuzhi; Bai, Bofeng
Graphical abstract: Highlights: NPG membranes present a high permeance and selectivity for hydrogen purification. An economic analysis is performed to evaluate the permeance-selectivity tradeoff. They have an excellent separation performance and impressive economic index. Abstract: We show from molecular dynamics insights that the nanoporous graphene (NPG) is an efficient membrane in hydrogen purification for separating gaseous H2 /CH4 mixtures with a high permeance and selectivity. The H2 permeance is as high as 10 6 GPU, extremely higher than those of polymer membranes; the selectivity of H2 over CH4 is up to 225, in the same order with those of polymer membranes. An economic analysis is performed from the aspects of compression energy consumption and required membrane area; it is shown that the NPG membrane requires less membrane area but a bit more compression energy compared with the polymer membranes. However, the slightly higher compression energy consumption can be totally offset by the remarkably smaller membrane area. In summary, the NPG membranes for hydrogen purification present an excellent separation performance with a high H2 permeance, ultimately resulting in an impressive economic index comparing to the polymer membranes.